Clinical characteristics of non‐ICU hospitalized patients with coronavirus disease 2019 and liver injury: A retrospective study. (12th April 2020) - Xie, Hansheng; Zhao, Jianming; Lian, Ningfang; Lin, Su; Xie, Qunfang; Zhuo, Huichang
Abstract: Background & Aims: Coronavirus disease 2019 (COVID‐19) has raised world concern for global epidemic since December, 2019. Limited data are available for liver function in COVID‐19 patients. We aimed to investigate the risk factors related to liver injury in the COVID‐19 patients. Methods: A retrospective study was performed in non‐ICU Ward at Jinyintan Hospital from February 2, 2020 to February 23, 2020. Consecutively confirmed COVID‐19 discharged cases were enrolled. The clinical characteristics of patients with liver injury and without liver injury were compared. Results: A total of 79 COVID‐19 patients were included. 31.6%, 35.4% and 5.1% COVID‐19 patients had elevated levels of alanine transaminase (ALT), aspartate aminotransferase (AST) and bilirubin respectively. Median value of ALT, AST and bilirubin for entire cohort was 36.5 (17.5 ~ 71.5) U/L, 34.5 (25.3 ~ 55.3) U/L and 12.7 (8.1 ~ 15.4) mmol/L respectively. There were no significant differences in age, previous medical history and symptoms between the two groups. Males were more likely to have liver injury when infected with COVID‐19 ( P  < .05); compared with patients without liver injury, patients with liver injury had increased levels of white blood cell counts, neutrophils, CRP and CT score ( P  < .05) and had a longer length of stay ( P  < .05). Logistic regression analyses suggested that the extent of pulmonary lesions on CT was a predictor of liver function damage ( P  < .05). Conclusions: Liver injury is common in non‐ICU hospitalized COVID‐19 patients. It may be related to systemic inflammation. Intense monitoring and evaluation of liver function in patients with severe pulmonary imaging lesions should be considered.